Performance Evaluation of a Rotary Paddy Power Weeder - Muhammed Ibrahim Binni; Abdulwahab M.; Ishaya Genesis; Zago Salisu Idris (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Weed infestation in paddy cultivation substantially constrains yield and profitability, especially where reliance on manual weeding remains time-consuming and costly. This study evaluates the performance of a rotary paddy power weeder powered by a 1.75 hp two-stroke petrol engine under wetland conditions, focusing on operational efficiency and economic feasibility. Field experiments were conducted at three forward speeds (1.58, 1.92, and 2.34 km/h) to assess weeding efficiency, plant damage, field capacity, fuel consumption, and post-weeding weed re-emergence. The results show that an intermediate forward speed of 1.92 km/h produced the best overall performance, achieving a weeding efficiency of 72.38% with minimal crop injury. Higher speeds increased field capacity but also elevated fuel consumption and reduced weeding quality, as the moving blades lacked sufficient dwell time for complete weed cutting. Cost analysis demonstrated that mechanized weeding with the rotary power weeder markedly reduced labor requirements and lowered weeding costs by approximately Rs. 2265 per hectare compared with manual methods. These findings indicate that rotary paddy power weeders offer a sustainable and economically viable alternative to manual weeding in paddy fields, supporting improved weed management and farm profitability.